SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI GOOD GOVERNANCE DI INDONESIA - Lina Agustina; M. Fachri Adnan; Syamsir Syamsir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Good governance, namely the administration of government that is effective, efficient, transparent, accountable, and responsible. This study aims to find out how the implementation of good governance in Indonesia is both theoretical and practical and how to solve it. With a systematic approach to Literature Review in journals that have been published from 2016 to 2021, the results show that current good governance research focuses on the topic of implementing the principles of good governance. The method that is often used in good governance research is a qualitative approach. The cause of problems in the implementation of good governance in Indonesia is the lack of transparency of the Indonesian government in meeting the needs of the community. solutions to problems in implementing good governance arestrengthening civil society groups is designed to make government institutional reforms transparent, accountable and efficient.Keywords: Systematics Literature Review, good governance.